UPAYA PENYIDIK PPA MELALUI DIVERSI GUNA MENDUKUNG PENYELESAIAN TINDAK PIDANA ANAK DI WILAYAH HUKUM POLRES KUDUS - Yuandhika Kresna Sang Damar (Advances in Police Science Research Journal, 2022)
ABSTRACT EFFORTS OF PPA INVESTIGATORS THROUGH DIVERSION TO SUPPORT THE SETTLEMENT OF CRIMINAL CRIMES IN THE UNIT OF KUDUS POLICE Yuandhika Kresna Sang Damar, 18.146, yuandhikaksd@gmail.com Child criminal cases are one of the conventional forms of crime that have increased in cases in Kudus Regency. The Criminal Investigation Unit, especially the PPA unit as the main implementer in law enforcement of crimes against children in the Kudus Polres area, plays a very important role in disclosing and resolving cases of child crimes so that the situation and conditions of the community become conducive as expected by the community. To identify the performance of the Criminal Investigation Unit, the authors carry out research of the implementation of diversion in the investigation of criminal acts of children in accordance with applicable regulations. The research was carried out using qualitative methods to obtain accurate data obtained through interviews, observations, and document studies, using primary and secondary data sources. Then the stages of data analysis used by the author are data reduction, data presentation, and drawing conclusions. The results showed that in practice, the investigators of the PPA of the Unit of Kudus Police were influenced by two (2) factors, namely internal and external factors. Internal factors that most influence the implementation of diversion in criminal investigations are the competence of investigators who do not have the knowledge, skills, and attitudes in accordance with the rules so that in their implementation they are still not as expected, while external factors that influence are suspects who are diverted in investigations are still classified as underage so it is easy to experience mental depression and psychological fear while at the police station and dealing with investigators during the examination process. The conclusion is that the sompetence of PPA investigators is still not maximizied in the process of implementing diversion through the criminal investigation process and the community’s efforts are still not visible due to the many factors and obstacle that occurs, so there’s need for quality improvement through training and development as well as the implementation of planning management, organizing, implementation and supervision as an effort to carry out diversion in the process of investigating criminal acts with child suspects